Tanggungjawab Hukum Bank Terhadap Nasabah dalam Hal Terjadinya Kegagalan Transaksi pada Sistem Mobile Banking - I Made Aditya Mantara Putra (Kertha Wicaksana, 2020)
In this era of millennial global era, of course we are familiar with the term mobile banking. Mobile banking is one of the ways in which internet is used for promoting and making transactions of traditional products such as opening deposit account, transferring funds to another account as well as new banking products such as claims through the bank websites. Two problems are formulated in this study. The first problem is how the costumers are legally protected when they make transactions trough mobile banking, to what extend the bank is responsible for the loss possibly resulting from any transaction through the mobile banking. This study is classified as a normative legal study. What is meant is that the data needed was obtained by library research, meaning that the data was obtained from the secondary sources. The problem were analyzed using legal interpretation followed by theoretical argument based on the legal theories and concepts available. The results of the study show that the customers in transacting with the mobile banking system even though there are no provisions governing legal protection specifically, customers are still given legal protection both preventive and repressive by the provisions contained in the legislation relating to banks and consumer protection. The results of the study show that the customers in transacting with the mobile banking system even though there are no provisions governing legal protection specifically, customers are still given legal protection both preventive and repressive by the provisions contained in the legislation relating to banks and consumer protectionThe bank will be responsible for providing compensation for any loss experienced by the customers resulting from the internet banking system, if the error made by the bank.